Characterization of poly (lactic-co-glycolic acid) / atelocollagen hybrid scaffold for intervertebral disc regeneration - Mohamad, Mohd Yusof; Mohamed Amin, Muhammad Azri Ifwat; Md Nazir, Noorhidayah; Ahmad Radzi, Muhammad Aa’zamuddin; Hashim, Rosyafirah; Mat Nawi, Nur Farhana; Zulkifly, Ahmad Hafiz; Sha'ban, Munirah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)

(untitled)
The objective of the present study is to characterize PLGA and atelocollagen type 2 (PLGA-A) hybrid scaffolds in terms of swelling capacity, thermal properties and mechanical strength. PLGA without atelocollagen was used as control.Porous PLGA scaffold is fabricated via salt leaching/ solvent-casting using salt at 350-400 micron. 1-Ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N-Hydroxysuccinimide (NHS) were used to crosslink atelocollagen with PLGA. The incorporation of atelocollagen and PLGA is confirmed by the presence of amide formation of amide bonds at 1650cm-1 using Fourier transform infrared spectroscopy (ATR-FTIR). Scanning Electron Microscopy (SEM) images demonstrated addition of atelocollagen did not jeopardize porous structure of PLGA scaffolds. Differential Scanning Calorimetry (DSC) analysis showed increment of glass transition, Tg of PLGA-A by 13°C. The swelling ratio of PLGA-A scaffold showed 4.8 times increase water uptake within 24-hour period. The mechanical strength of PLGA-A is enhanced by 255.95% when tested with Instron E3000 machine. These findings suggest PLGA incorporation with atelocollagen type 2 may become a promising biomaterial for intervertebral disc regeneration.